2017
DOI: 10.1007/s10943-017-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Behind Religiosity and Spirituality’s Effect on Mental Health, Quality of Life and Well-Being

Abstract: This cross-sectional study aims to evaluate the role of meaning, peace, faith and religiosity on mental health, quality of life (QOL) and well-being in 782 adults. We found associations between (a) meaning and peace with less depression and more QOL, (b) peace with less stress and (c) faith and religiousness with more psychological QOL. Meaning and peace were more strongly associated with health outcomes, and those with high levels of intrinsic religiosity but low levels of meaning/peace have worse outcomes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 43 publications
4
48
0
6
Order By: Relevance
“…Religion is one of the factors that affects successful aging . In the literature, it is reported that spirituality, belief and trust in God are important for successful aging and life satisfaction . Studies have shown that religion enables people to have an optimistic worldview and that people who are more religious are happier and more satisfied with life .…”
Section: Discussionmentioning
confidence: 99%
“…Religion is one of the factors that affects successful aging . In the literature, it is reported that spirituality, belief and trust in God are important for successful aging and life satisfaction . Studies have shown that religion enables people to have an optimistic worldview and that people who are more religious are happier and more satisfied with life .…”
Section: Discussionmentioning
confidence: 99%
“…It shows the role of religion in the search process of life meaning and peaceful feelings. People with higher levels of religiality have a greater sense of peace than people with lower religiusidity [13]. There is a decrease in both systolic and diastolic blood pressure in the group of progressive muscle relaxation.…”
Section: Methodsmentioning
confidence: 95%
“…Some scholars divide religious practice into private (interiorised) or public (exteriorised) religiosity. 12,13 Private religiosity refers to factors occurring alone or in the family home, for example, reading scripture or private prayer. Public religiosity refers to communal religious activities such as attending a place of worship or group study of a sacred text.…”
Section: Public and Private Religiositymentioning
confidence: 99%